The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.15406/mojs.2017.04.00057
|View full text |Cite
|
Sign up to set email alerts
|

Early Recovery after Small Bowel Surgery

Abstract: Background: Bowel anastomoses are common procedures in both elective and emergency general surgery Therefore, the aim of this study was to assess the safety, tolerability and outcome of early oral feeding after small bowel anastomosis.Methodology: This is a Quasi experimental study conducted at Surgical unit (ward 26) Jinnah postgraduate medical center, Karachi, Pakistan, during the period from March 2014 to November 2016. In the present study we investigated 59 cases, their ages ranging from 17-45years.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Early oral feeding after perforated duodenal ulcer repair did not result in the repair site leak in any patients. A previous study reported that primary small bowel anastomosis in emergency cases also showed encouraging results if patients are properly selected and operated upon by experienced surgeons [9].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Early oral feeding after perforated duodenal ulcer repair did not result in the repair site leak in any patients. A previous study reported that primary small bowel anastomosis in emergency cases also showed encouraging results if patients are properly selected and operated upon by experienced surgeons [9].…”
Section: Discussionmentioning
confidence: 95%
“…Traditional postoperative care has been practised for many years in elective and emergency abdominal surgeries with protocols that allow oral feeding after three to five days following perforated duodenal ulcer repair or gut anastomosis. This protocol allows the repair site to heal and normal gut peristalsis to resume, so repair site leak chances are minimized [9]. Part of the reason why this approach has been so broadly adopted is that repair site leak is a surgeon's nightmare.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative care has been practised for many years with protocols that manadate oral nutrition after three to ve days following perforated duodenal ulcer repair or any gastrointestinal anastomosis [7].…”
Section: Discussionmentioning
confidence: 99%